El Salvador Financial Sector Assessment Program Development Module : Efficiency and Competition - World Bank (World Bank, Washington, DC, 2017)
This technical note was prepared in the context of a World Bank Financial Sector Assessment Program mission in the Republic of El Salvador in March 2016. The Salvadoran financial system lags behind its peers in terms of depth put it outperforms them in terms of competition and efficiency. Given the country’s relative low financial depth but competitive environment, there is room for expansion and financial development which can provide greater funding for the productive activities of the private sector. This technical note takes four main approaches to examine the extent of competition and efficiency of the Salvadoran banking sector. First, it examines bank entry and exit regulations and bank transparency to determine whether the existing framework promotes contestability and competition. Second, the note evaluates the degree of concentration in the banking sector and estimates direct measures of competition by calculating the H-statistic for the Salvadoran banking sector and by comparing it to those obtained for its regional peers. Third, the note evaluates efficiency by examining the behavior of bank spreads, profitability and financial intermediation margins and costs. Fourth, the note looks into the different segments of the loan market to evaluate how efficiently credit is being allocated. Finally the note ends with some policy recommendations. The document contains technical analysis and detailed information underpinning the FSAP assessment’s findings and recommendations. Further information on the FSAP program can be found at www.worldbank.org/fsap.